1990
DOI: 10.2135/cropsci1990.0011183x003000010019x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine Fumigation Influence on Rice Seed Germination and Vigor

Abstract: Fumigation of seeds is one of the quarantine precautions directed against the international spread of pests. Seed treatment should ward off the pests without hampering seed germination and vigor. A study was conducted to evaluate the effect of fumigation with phosphine at different doses, exposure times, and seed moisture contents, and after the seed has been treated with fungicides on seed germination and seedling vigor in rice (Oryza sativa L.). The fumigated seed was evaluated for germination and vigor, ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 0 publications
0
41
0
1
Order By: Relevance
“…Rihane-05//As46/Aths*2" Aths/ Lignee686 Line-1 Lignee527/Aths//Lignee527/NK1272/3/Arar/Rhn-03 Line-2 Giza126/3/Lignee527/NK1272//Alanda/6/Lignee527// Bahtim/DL71/3/Api/CM67//Mzq/5/Alanda-01/4/ WI2291/3/Api/CM67//L2966-69 Line-3 ACSAD1182/4/Arr/ESP//Alger/Ceres362-1-1/3/WI/6/Lignee527//Bahtim/ DL71/3/Api/CM67//Mzq/5/ Ager//Api//CM67/3/Cel/WI2269// Ore/4/Hamra-01 Line-4 Alanda/Harma//Alanda-01/3/ACSAD1612 Line-5 Alanda/Hamra//Alanda-01//Giza 2000 Shoot and root length(cm): Measured as the mean of ten normal seedlings 14 days after planting Seedling dry weight(g): Ten normal seedlings were dried in a hot-air oven at 85°C for 12 h to obtain the seedling dry weight (g) according to Krishnasamy and Seshu (1990). K + and Na+ (mg/dry weight) were determined according to (Jackson, 1973).…”
Section: Genotypementioning
confidence: 99%
“…Rihane-05//As46/Aths*2" Aths/ Lignee686 Line-1 Lignee527/Aths//Lignee527/NK1272/3/Arar/Rhn-03 Line-2 Giza126/3/Lignee527/NK1272//Alanda/6/Lignee527// Bahtim/DL71/3/Api/CM67//Mzq/5/Alanda-01/4/ WI2291/3/Api/CM67//L2966-69 Line-3 ACSAD1182/4/Arr/ESP//Alger/Ceres362-1-1/3/WI/6/Lignee527//Bahtim/ DL71/3/Api/CM67//Mzq/5/ Ager//Api//CM67/3/Cel/WI2269// Ore/4/Hamra-01 Line-4 Alanda/Harma//Alanda-01/3/ACSAD1612 Line-5 Alanda/Hamra//Alanda-01//Giza 2000 Shoot and root length(cm): Measured as the mean of ten normal seedlings 14 days after planting Seedling dry weight(g): Ten normal seedlings were dried in a hot-air oven at 85°C for 12 h to obtain the seedling dry weight (g) according to Krishnasamy and Seshu (1990). K + and Na+ (mg/dry weight) were determined according to (Jackson, 1973).…”
Section: Genotypementioning
confidence: 99%
“…Increased sorption will increase fluoride residue levels and further inhibit germination by the mechanism described. Of the common fumigants used world-wide, phosphine (Bond 1984) has been found to have no effect on wheat and rice germination (Bakheit et al 1985;Krishnasamy and Seshu 1990), whereas methyl bromide can have a significant impact on germination (Bond 1984). For example, onion seed germination was reduced by fumigation with different concentrations of methyl bromide (Powell 1975), and a significant reduction of up to 90% was recorded.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, other researchers reported no reduction in germination percentage when using methyl bromide on wheat (Lubatti and Blackith 1957;Whitney et al 1958;Orth et al 1977). Furthermore, fumigating rice, corn, and wheat with phosphine also did not affect germination (Lindgren et al 1958;Cogburn and Tilton 1963;Bakheit et al 1985;Krishnasamy and Seshu 1990). In regard to grain quality attributes, applying commercial doses of methyl bromide to wheat, wheat flour, or milled flour from fumigated wheat did not change bread baking characteristics (Shepard and Buzicky 1939;Hermitte and Shellenberger 1947;Matthews et al 1970;Orth et al 1977).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It generally retains very low residue in grains. Krishnasamy and Seshu (1990) examined the effect of phosphine fumigation on vigor and germination of 27 rice varieties and found that there is no influence of phosphine on grains at about 2,000 ppm, initially, after treatment, and upon storage. Only when the concentration is increased greater than 4,000 ppm, a reduction in seed germination and vigor was observed.…”
Section: Existing Disinfestation Techniquesmentioning
confidence: 99%